Mind the gap: Inequalities in mental health care and lack of social support in Parkinson disease. (December 2021) - Subramanian, Indu; Hinkle, Jared T.; Chaudhuri, K. Ray; Mari, Zoltan; Fernandez, Hubert H.; Pontone, Gregory M.
Abstract: Inequalities in mental healthcare and lack of social support during the COVID-19 pandemic have lowered quality of life and increased overall burden of disease in people with Parkinson's (PWP). Although the pandemic has brought attention to these inequalities, they are long standing and will persist unless addressed. Lack of awareness of mental health issues is a major barrier and even when recognized disparities based on race, gender, and socioeconomic factors limit access to already scarce resources. Stigma regarding mental illness is highly prevalent and is a major barrier even when adequate care exists. Limited access to mental healthcare during the pandemic and in general increases the burden on caregivers and families. Historically, initiatives to improve mental healthcare for PWP focused on interventions designed for specialty and academic centers generally located in large metropolitan areas, which has created unintended geographic disparities in access. In order to address these issues this point of view suggests a community-based wellness model to extend the reach of mental healthcare resources for PWP. Highlights: COVID-19 has unmasked unmet mental health needs in Parkinson's disease (PD). Disparities in care exacerbate challenges for PD patients from minority populations. Wellness strategies may have a role in proactively improving mental health in PD.